Rancang Bangun Sistem Informasi Perpustakaan SMA/SMK Menggunakan Metode Extreme Programming - M. Ari Prayitno; Edi Saputra; Muhammad Razi A.; Niko Akbar; Putri Hazmawati; Adfa Aditiya (Lembaga Pengembangan Kinerja Dosen, 2025)
Developing a Library Information System can enhance the efficiency of library data management. The background of this research stems from the fact that many school libraries still encounter various challenges in their operational activities. For instance, SMK Negeri 6 Kota Jambi still implements a manual management system. Meanwhile, SMA Negeri 2 Kota Jambi utilizes SLIMS, which has been found to be difficult to understand and not user-friendly for library administrators. As a result, the administrators decided to revert to manual record-keeping using library logbooks. Similarly, SMA Negeri 3 Kota Jambi employs INLISLITE; however, its book borrowing and returning features are not functioning properly, and the system frequently experiences technical issues. To address these problems, this study proposes the development of a Library Information System using the Extreme Programming (XP) methodology. Extreme Programming is a software development method known for its adaptability to changing user requirements and its ability to support rapid and flexible system development processes. The purpose of this research is to implement a library information system capable of efficiently managing data, book borrowing and returning processes, as well as searching for book and room information. Additionally, the system provides a platform for library members to publish content. To ensure that the developed system meets the intended expectations, Black Box Testing is applied as the testing method. Based on the testing results, the system functions properly, as indicated by a 100% success rate in Black Box Testing outcomes.